A Revisit to Estimating Phillips Curve and NAIRU in Pakistan - Tauseef, Tahira; Chaudhary, Amtul R.; Tauheed, Tahira (iRASD Journal of Economics, 2024)
This paper investigates the conventional Philips curve within the unique economic context of Pakistan, traditionally employed to analyze the intricate interplay between inflation and unemployment. Utilizing the Autoregressive Distributed Lag (ARDL) methodology, the research integrates annual data spanning from 1991 to 2022 on core inflation, unemployment, and supply shocks to estimate the Philips curve. Two distinct specifications of the Philips curve—the new Keynesian and the Triangle model—are employed to capture nuanced relationships. Moreover, the study establishes a constant Non-Accelerating Inflation Rate of Unemployment (NAIRU) derived from the estimated Philips curve, with precision assessed using Delta and Fieller methods. The empirical results robustly affirm the presence of a long-term trade-off between inflation and unemployment, offering fresh insights into Pakistan’s economic dynamics. The ARDL error correction model reveals that short-term inflation dynamics are primarily influenced by inertia. At the same time, long-term trends are dictated by unemployment and the import price index, with the industrial productivity index deemed insignificant. The calculated sacrifice ratios of 0.57 and 0.51, alongside NAIRU estimates of 5.7 and 5.0 for the New Keynesian and Triangular models, respectively, signal a need for caution in implementing anti-inflationary policies. Addressing the significant impact of demand gaps and supply shocks on inflation calls for policies to reduce supply-demand disparities. Maintaining an optimal equilibrium of inflation and unemployment (NAIRU) necessitates a combination of stabilization and adverse supply shock control policies. These findings underscore the stabilizing role of commercial policy and advocate for reforms to bolster Pakistan’s industrial sector.